The Effect of Font Size on Children’s Memory and Metamemory - Halamish, Vered; Nachman, Hila; Katzir, Tami (Frontiers in Psychology, 2018)
Recently, there has been a growing interest in the effect of perceptual features of learning materials on adults' memory and metamemory. Previous studies consistently have found that adults use font size as a cue when monitoring their learning, judging that they will remember large font size words better than small font size words. Most studies have not demonstrated a significant effect of font size on adults' memory, but a recent meta-analysis of these studies revealed a subtle memory advantage for large font words. The current study extended this investigation to elementary school children. First and fifth–sixth graders studied words for a free recall test presented in either large or small font and made judgments of learning (JOLs) for each word. As did adults, children predicted they would remember large font size words better than small font size words and, in fact, actually remembered the large font size words better. No differences were observed between the two age groups in the effect of font size on memory or metamemory. These results suggest that the use of font size as a cue when monitoring one's own learning is robust across the life span and, further, that this cue has at least some validity.